2022
DOI: 10.3390/v14040723
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Total Antioxidant Capacity and Carbonylated Proteins Are Increased in Pregnant Women with Severe COVID-19

Abstract: Oxidative stress (OS) induced by SARS-CoV-2 infection may play an important role in COVID-19 complications. However, information on oxidative damage in pregnant women with COVID-19 is limited. Objective: We aimed to compare lipid and protein oxidative damage and total antioxidant capacity (TAC) between pregnant women with severe and non-severe COVID-19. Methods: We studied a consecutive prospective cohort of patients admitted to the obstetrics emergency department. All women positive for SARS-CoV-2 infection b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Likewise, SARS-Cov-2 infection and acute COVID-19 are accompanied by an inflammatory response 29 , increased MPO activity 35 , indicants of oxidative damage [36][37][38] and increased NO production including increased levels of nitrotyrosine 39 , and lowered antioxidant defenses as indicated by reduced TAC levels 35,39 , Gpx 40 and zinc 41 . Nevertheless, there are no data on whether the effects of the immune-inflammatory processes during acute infection, as indicated by lowered SpO2 and increased body temperature on the physio-affective phenome, are mediated by activated immune and O&NS (IO&NS) pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, SARS-Cov-2 infection and acute COVID-19 are accompanied by an inflammatory response 29 , increased MPO activity 35 , indicants of oxidative damage [36][37][38] and increased NO production including increased levels of nitrotyrosine 39 , and lowered antioxidant defenses as indicated by reduced TAC levels 35,39 , Gpx 40 and zinc 41 . Nevertheless, there are no data on whether the effects of the immune-inflammatory processes during acute infection, as indicated by lowered SpO2 and increased body temperature on the physio-affective phenome, are mediated by activated immune and O&NS (IO&NS) pathways.…”
Section: Introductionmentioning
confidence: 99%
“…However, the level of this enzyme was lower in the lungs and has only been detected in some inflammatory cells [17]. In addition, it was suggested that the observed enhancement of total antioxidant capacity (TAC) in pregnant women with COVID-19 may be the body's response to damage to cellular components caused by excess ROS [18]. One of the main consequences of oxidative stress is the modification of physiological lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of soluble FLT‐1, we included 6 studies 13,48,66,68–70 with 190 patients in poor outcome group and 471 patients in good outcome group. The meta‐analysis derived a pooled standard mean difference of 1.93 (0.65, 3.21) ( p = 0.003).…”
Section: Resultsmentioning
confidence: 99%
“…Both VEGF and sFLT-1 have previously shown to be associated with sepsis progression, severity and mortality as well as organ dysfunction in these patients. 1,12 Several studies have investigated possible role of these markers in COVID-19 patients and whether they can be used as predictors of severity and mortality of COVID-19 9,13,[66][67][68] . Pine et al…”
Section: Syndecan-1mentioning
confidence: 99%